Career calling, ethical sensitivity, and decision-making ability in intensive care nurses: a mediating effect model - Wang, Ke; Mi, Yuanyuan; Wu, Yanli; Sun, Huimin (Frontiers in Psychology, 2025)
AimsTo investigate the simultaneous effects of ethical sensitivity and career calling on intensive care nurses’ decision-making ability.MethodsA total 361 intensive care nurses in Hubei Province were selected as survey subjects. The survey employed a general information questionnaire, a nurse career calling scale, a Chinese version of the nursing ethics decision-making ability questionnaire, and an ethics sensitivity questionnaire. A structural equation model was constructed using the AMOS software.ResultsThe ethical decision-making ability of intensive care nurses earned a score of (267.62 ± 28.15). Ethical sensitivity (r = 0.584, p < 0.001) and career calling (r = 0.566, p < 0.001) positively correlated with ethical decision-making ability in nursing. Career calling partially mediates between ethical sensitivity and nursing ethical decision-making ability, with a mediation effect of 0.246.ConclusionIntensive care nurses exhibited moderate ethical decision-making ability and require further improvement. Career calling partly mediates between moral sensitivity and nursing ethical decision-making ability. Enhancing ethical sensitivity and career calling can help improve ethical decision-making ability among intensive care nurses.